Frequent cleft lip and palate in families with pathogenic germline CDH1 variants - Green, Benjamin L.; Fasaye, Grace-Ann; Samaranayake, Sarah G.; Duemler, Anna; Gamble, Lauren A.; Davis, Jeremy L. (Frontiers in Genetics, 2022)
Pathogenic and likely pathogenic (P/LP) germline variants in the tumor suppressor gene CDH1 (E-cadherin) result in increased lifetime risk of diffuse-type gastric cancer and lobular breast cancer. CDH1 variants are also associated with hereditary cleft lip and palate (CLP), the mechanism of which is not well understood. We sought to determine the prevalence of CLP in families who carry P/LP CDH1 variants. Medical records of patients with P/LP CDH1 variants who were enrolled in a prospective clinical trial were reviewed (NCT03030404). The cohort included 299 individuals from 153 families that had 80 unique P/LP variants in CDH1. The rate of CLP was 19% (29/153) in families reporting CLP in at least one family member, and 2.7% (8/299) among enrolled individuals with germline CDH1 P/LP variants. There were 22 unique variants in CDH1 among the 29 families that reported CLP, or a CLP rate of 27.5% per variant (22/80). 10 of the variants were not previously reported to be associated with CLP. Many CLP-associated gene variants involved large-scale (≥1 exon) deletions. Among families with CLP, 69% (20/29) had a member diagnosed with gastric cancer, and 79% (23/29) had a member with breast cancer, similar to rates observed in non-CLP families (p>0.3 for both). Our analysis suggests that the prevalence of CLP in families with germline CDH1 P/LP variants was high in this large cohort, and there was no genotype-phenotype pattern. Genetic testing for CDH1 variants should be considered in families with CLP and history of diffuse-type gastric or lobular breast cancer.